TanDEM-X: The New Global DEM Takes Shape - Zink, Manfred; Bachmann, Markus; Braeutigam, Benjamin; Fritz, Thomas; Hajnsek, Irena; Krieger, Gerhard; Moreira, Alberto; Wessel, Birgit (IEEE Geoscience and Remote Sensing Magazine, 2014)
TanDEM-X (TerraSAR-X add-on for Digital Elevation Measurements) is an innovative formation flying radar mission that opens a new era in spaceborne radar remote sensing. The primary objective is the acquisition of a global Digital Elevation Model (DEM) with unprecedented accuracy (12 m horizontal resolution and 2 m relative height accuracy). This goal is achieved by extending the TerraSAR-X synthetic aperture radar (SAR) mission by a second, TerraSAR-X like satellite TanDEM-X (TDX) flying in close formation with TerraSAR-X (TSX). The resulting large single-pass SAR interferometer features flexible baseline selection enabling the acquisition of highly accurate cross-track interferograms not impacted by temporal decorrelation and atmospheric disturbances. Beyond the global DEM, several secondary mission objectives based on alongtrack interferometry as well as new bistatic and multistatic SAR techniques have been defined. © 2013 IEEE.
DLR Import::2019-04-02